Estrogens and regucalcin in testicular apoptosis and sperm function: “a matter of life and death". - Correia, Sara Carina de Lima (2014)
Spermatogenesis is the intricate and coordinated process by which thousands of spermatozoa are produced daily within the male gonad. In addition, mammalian testis also serves as an endocrine organ, producing the sex steroid hormones needed for normal spermatogenesis and development of male phenotype. Over the years, estrogens have emerged as important regulators of male reproductive function, but their role in spermatogenesis has remained a matter of controversy. There are reports indicating that estrogens are survival factors for germ cells, while other strong evidences associated their actions with testicular apoptosis and diminution of germ cell number. Furthermore, the molecular targets underpinning the survival or apoptotic effects of estrogens in mammalian testis remain to be fully elucidated. Regucalcin (RGN) is a calcium (Ca2+)‐binding protein playing an important role in the maintenance of intracellular Ca2+ homeostasis, for which a role in spermatogenesis has been suggested. RGN was identified in male reproductive tract tissues, being described as an estrogen‐target gene in rat and human prostate cells, and as an androgen‐target gene in the testis. However, the effect of estrogens controlling the expression levels of RGN in the testis is entirely unknown. Noteworthy, it has been indicated the role of RGN in the control of cell survival and apoptosis, and its antioxidant properties also have been reported. Although a tight control of apoptosis and oxidative stress are of the paramount importance for proper testis function, the role of RGN in testicular physiology has not deserved attention yet. Sperm undergo maturation acquiring progressive motility and the capacity to fertilize oocyte only during passage through the epididymis. Although a gradient of Ca2+ along the epididymis has been described, its effects on epididymal function remain poorly explored. The main objective of this thesis is to disclose the relationship between estrogens and apoptosis of germ cells, including the regulatory effects of these sex steroid hormones on the testicular expression of RGN. Secondly, the role of RGN in regulating apoptosis and oxidative stress in the testis, as well as, in sperm maturation in epididymis will be explored. A 100 nM dose of 17β‐estradiol (E2), mimicking the elevated concentrations of estrogens found in the testis of infertile patients, induced apoptosis of germ cells and decreased cell proliferation, which was accompanied by disrupted expression of the SCF/c‐kit system. E2‐ stimulation also increased RGN expression, suggesting that the augmented expression of this protein may be a mechanism to counteract E2‐induced apoptosis. Concerning the function of RGN in modulation of apoptosis in the testis, it was shown that RGN plays a pivotal role rescuing cells from apoptosis induced by noxious stimuli. Moreover, RGN overexpression led to increased protection against oxidative stress in the testis, which further confirmed the cytoprotective role of RGN. The results presented herein also demonstrated the importance of maintaining Ca2+ levels in the epididymal lumen and supported a role for RGN in sperm maturation. In conclusion, the present thesis demonstrated that elevated concentrations of estrogens may unbalance the expression of SCF/c‐kit system leading to depletion of germ cells due to augmented apoptosis and decreased proliferation, which has contributed to understand the molecular basis of hyperestrogenism related male infertility. These findings also provided a rationale to explain the successful use of aromatase inhibitors to treat male infertility, and suggested that manipulation of c‐kit and RGN levels may be a possible mechanism to preserve germ cell integrity and fertility. Thus, the action of estrogens and RGN on testis physiology and sperm function has emerged as “a matter of life and death”.